The Untold Stories of Thai High-school Non-readers of the English Language: A Narrative Inquiry - Laguyo, Hyatt Ali (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aimed to explore the untold stories of non-readers in Thailand to gain a deeper understanding of the persistent existence of non-reading. Using a qualitative design, I collected, gathered, analyzed, interpreted, and provided data results to achieve the research purpose and offered further recommendations. This study employs a narrative inquiry approach to explore the stories and experiences of non-readers, aiming to uncover new ideas and understandings about non-reading through an interactive process. In this study, I worked with participants who are non-readers. The number of participants in this study was determined based on the saturation point. The saturation point is when no new information is learned from the interviews. The results of this study highlight the complex relationship between linguistic, pedagogical, and sociocultural elements that impact the development of English literacy in Thai high school students. These findings underscore the multifaceted challenges Thai high-school non-readers face in developing English reading proficiency, pointing to the need for tailored interventions and enhanced teacher support to foster inclusive and effective learning environments. The complex interplay of educational, sociocultural, and pedagogical factors shaping the English literacy journey of Thai high-school students, highlighting the need for targeted interventions and support mechanisms to foster inclusive and effective learning environments.